Factors associated with workplace violence against Chinese healthcare workers: an online cross-sectional survey - Xiao, Yu; Chen, Ting-ting; Zhu, Shao-yi; Li, Chun-ya; Zong, Ling (Frontiers in Public Health, 2024)
Objectives: Workplace violence (WPV) against healthcare workers (HCWs) has reached significant levels globally, impeding the quality and accessibility of healthcare systems. However, there is limited available knowledge regarding the determinants linked with WPV among HCWs and the discrepancies observed across various levels of hospitals in China. The objective of the present research was to investigate the factors linked to WPV and job satisfaction among HCWs in China.A self-developed questionnaire based on WeChat was employed to collect data. The questionnaire consisted of demographic information as well as occupational factors. To measure WPV, the Chinese version of the Workplace Violence Scale was utilized. Career satisfaction was assessed through two questions regarding career choices. The collected data was analyzed using descriptive analyses, chi-square tests, and multivariate logistic regressions.Results: A total of 3781 valid questionnaires (1029 doctors and 2752 nurses) were collected. Among all participants, 2201 (58.2%) reported experiencing at least one form of WPV in the past year, with emotional abuse being the most frequent occurrence (49.7%), followed by threats (27.9%). The multivariate logistic regression analysis revealed several risk factors associated with WPV, including male gender, shift work, senior professional title, bachelor's degree education, employment in secondary-level hospitals, and working over 50 hours per week (P < 0.05). Career satisfaction among HCWs who experienced high levels of WPV was low, with only 11.2% remaining confident in their profession, and a mere 2.0% supporting their children pursuing careers in healthcare.Conclusions: WPV poses a significant challenge within the Chinese healthcare system. Efforts should be made to address the identified risk factors and promote a safe and satisfying working 2 environment for HCWs.